The Concept of Equivalence and Translation Techniques in the Poststructuralists’ Theories of Translation - Salmeri, Claudio (Respectus Philologicus, 2015)
This article studies the development of the translation theories in the second half of the twentieth century, a period during which significant theoretical contributions were made in translation circles. These contributions had a profound impact on the practice of translation. The individuals who contributed to the present state of translation theory worked in translation circles, and this article examines their contributions. A selected history of theoretical developments, focusing on the most important ideas relevant to translation work, is presented in order to examine the impact of such theories on the practice of translation. It has become commonplace to believe that the deconstructionist and poststructuralist views on translation have opened new perspectives in Translation Studies. The aim of this paper is to highlight the main tenets of the major authors of these theories. The attention is especially drawn to a well-known controversy related to the concept of equivalence and translation strategies. This paper presents the main criticism made by the poststructuralist translation views on interpretation. Finally, some conclusions are drawn.